Exploring digital time measurement in the public sector: Labor productivity and service quality in home care - Henrik Jordahl; Lovisa Persson (Research Institute of Industrial Economics (IFN), 2018)
We measure labor productivity in home care using new data from the recent introduction of digital time measurement in Swedish municipalities. By measuring worker utilization (delivered hours as a share of worked hours) we avoid several problems that have plagued previous studies of public sector productivity. The time use measure exposes substantial variation in productivity between home care units, suggesting room for improvement. More productive units deliver a larger share of the hours approved by care managers and have equally satisfied users.
Keywords: H42; H45; L33; 330; Public sector productivity; Digitalization; Time use; Choice reforms